2009
DOI: 10.1590/s0066-782x2009001100014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil nutricional e cardiovascular de ratos normotensos e hipertensos sob dieta hiperlipídica

Abstract: Although it had not significantly affected the nutritional profile of the SHR, the treatment increased cardiac remodeling and precipitated the emergence of ventricular diastolic dysfunction. In WKY, the diet increased adiposity and leptinemia, and promoted non-significant cardiovascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…These results are consistent with studies on the effects of combined hypertension and DM in mice [10] and SHR [52]. It should be pointed out that, although we found no significant differences in collagen content between SHR and SHR-DM, both groups presented increased myocardial fibrosis against literature data from normotensive rats [18,53,54]. Therefore, we can conclude that additional fibrosis is not involved in diabetes-induced impaired cardiac function in SHR.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with studies on the effects of combined hypertension and DM in mice [10] and SHR [52]. It should be pointed out that, although we found no significant differences in collagen content between SHR and SHR-DM, both groups presented increased myocardial fibrosis against literature data from normotensive rats [18,53,54]. Therefore, we can conclude that additional fibrosis is not involved in diabetes-induced impaired cardiac function in SHR.…”
Section: Discussionsupporting
confidence: 92%
“…Within these studies, the data collectively suggest that Wistar and SD rats have distinct lipid metabolism,[20] and Wistars may develop myocardial pathology with shorter dietary interventions [70], [76]. Additional strain differences in metabolic and myocardial responses to high-fat feeding have been demonstrated [77]. Our findings provide evidence for a strain effect on feed efficiency, body weight, heart rate and serum adiponectin and the myocardial FA profile.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, Carroll et al 9 , found no change in the fraction of total collagen in obese rats subjected to a high-fat diet for 12 weeks. Previous studies carried out in our laboratory showed that Wistar rats made obese by a 15-week high fat diet 10 and Wistar-Kyoto rats made obese by 20-week high fat and carbohydrate diet 11 showed increased myocardial total collagen. In these studies, however, the fractions of collagen types I and III were not evaluated.…”
Section: Introductionmentioning
confidence: 71%